An overview of the studies on microbial air contamination in operating theatres and related issues over time: a useful tool for a multidisciplinary approach - Albertini, Roberto; Coluccia, Alessia; Colucci, Maria Eugenia; Zoni, Roberta; Affanni, Paola; Veronesi, Licia; Pasquarella, Cesira (Acta Biomedica Atenei Parmensis, 2023)
Background and aim Surgical site infection (SSI) is a major complication following surgery associated with increased morbidity and mortality, as well as increased health and not health costs. A variety of factors affect airborne contamination in operating theatres (OT). Following the Medical Research Council study showing a correlation between microbial air contamination and SSI incidence in prosthetic joint surgery ultraclean OTs have been recommended for this type of surgery, while OTs supplied by turbulent airflow plants are recommended for other types of surgery. The aim of this study was to illustrate the studies on this topic.MethodsScopus was considered for articles published until January 2023 on OTs and air contamination in article title or abstract or keywords. Many issues were deepened: “microbial”, “bacterial”, “fungi”, “viruses”, “surgical site/wound infection”, “monitoring/sampling”, “air changes”, “behaviour”, “door openings”, “particles”, turbulent flow”, “unidirectional flow”.ResultsTotal papers published were 907 and 249 papers faced monitoring/sampling. A total of 313 papers investigated airborne bacterial contamination and 63 papers investigated fungal air contamination. There were 218 papers that have evaluated particle contamination in OTs. Many other issues were deepened.ConclusionsThis study shows a picture of the studies on biological air contamination in OTs and related issues over time. We think that the results of our study will provide a useful tool to increase awareness towards a better sharing of aims, approaches, and results, above all in the interest of the patients, but also of the health services of the different countries. (www.actabiomedica.it)